Neural bases of social deficits in ADHD: A systematic review. Does the Theory of Mind matter - Novak, Lukas; Malinakova, Klara; Trnka, Radek; Mikoska, Petr; Sverak, Tomas; Kiiski, Hanni; Tavel, Peter; van Dijk, Jitse P (Brain research bulletin, 2024)
INTRODUCTION: The Attention Deficit Hyperactivity Disorder (ADHD) causes serious interpersonal problems from childhood to adulthood, one of them being problematic social functioning. This phenomenon in ADHD should be associated with impairments in the Theory of Mind (ToM). Therefore, understanding the neural correlates of the ToM could be crucial for helping individuals with ADHD with their social functioning. Thus, we aimed to review published literature concerning neuroanatomical and functional correlates of ToM deficits in children and adolescents with ADHD. METHODS: We reviewed studies published between 1970 and 2023. In accordance with PRISMA guidelines, after data from three databases were collected, two authors (LN and PM) independently screened all relevant records (n=638) and consequently, both authors did the data extraction. The quality of the included studies (n=5) was measured by a modified version of The Newcastle-Ottawa Scale and by measures specific for our study. This systematic review was registered on PROSPERO (CRD42020139847). RESULTS: Results indicated that impairments in performing of the ToM tasks were negatively associated with the grey matter volume in the bilateral amygdala and hippocampus in both, ADHD and control group. In EEG studies, a significantly greater electrophysiological activity during ToM tasks was observed in the, frontal, temporal, parietal and occipital lobes in participants with ADHD as compared to healthy subjects. CONCLUSION: More research is needed to explore the ToM deficits in children with ADHD. Future research might focus on the neural circuits associated with attention and inhibition, which deficits seems to contribute to the ToM deficits in children and adolescents with ADHD.
Keywords: elektroencefalografie; dítě; Attention Deficit Disorder with Hyperactivity; lidé; mladiství; mozek; Brain; Electroencephalography; Theory of Mind; Child; teorie mysli; Humans; Adolescent; hyperkinetická porucha